2012
DOI: 10.1007/s13181-011-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Death Following Recreational Use of Designer Drug “Bath Salts” Containing 3,4-Methylenedioxypyrovalerone (MDPV)

Abstract: Introduction 3,4-Methylenedioxypyrovalerone (MDPV) is a designer stimulant drug that has gained popularity in the USA. Although adverse effects of MDPV have been described, to our knowledge, this is the first reported death. Case Report We report the case of a 40-year-old male who injected and snorted "bath salts" containing MDPV and subsequently became agitated, aggressive, and experienced a cardiac arrest. He was resuscitated after his initial arrest; however, he developed hyperthermia, rhabdomyolysis, coagu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 246 publications
(128 citation statements)
references
References 21 publications
(23 reference statements)
3
122
0
3
Order By: Relevance
“…A variety of designer cathinone derivatives and other substances (eg, caffeine) can be found in bath salts products, but MDPV is the main compound detected in biological fluids from patients admitted to emergency departments for bath salts overdose in the United States (Borek and Holstege, 2012;Kyle et al, 2011;Murray et al, 2012;Spiller et al, 2011). We found that MDPV is a catecholamine-selective transporter blocker that is much more potent than cocaine when assessed using in vitro transporter assays.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…A variety of designer cathinone derivatives and other substances (eg, caffeine) can be found in bath salts products, but MDPV is the main compound detected in biological fluids from patients admitted to emergency departments for bath salts overdose in the United States (Borek and Holstege, 2012;Kyle et al, 2011;Murray et al, 2012;Spiller et al, 2011). We found that MDPV is a catecholamine-selective transporter blocker that is much more potent than cocaine when assessed using in vitro transporter assays.…”
Section: Discussionmentioning
confidence: 63%
“…Although some cathinone derivatives are legal and can be sold without penalty, three of the most popular drugs of this type-3,4-methylenedioxypyrovalerone (MDPV), 4-methylmethcathinone (mephedrone), and 3,4-methylenedioxymethcathinone (methylone)-have been classified as Schedule I-controlled substances in the United States (DEA, 2011). All three of the Schedule I cathinones, depicted in (Figure 1), have been identified in bath salts products (Ross et al, 2011;Spiller et al, 2011), but MDPV is the chief substance found in the blood and urine from patients exposed to bath salts who are admitted to emergency departments in the United States (Borek and Holstege, 2012;Kyle et al, 2011;Murray et al, 2012;Spiller et al, 2011). The available evidence suggests that MDPV is a primary culprit in mediating adverse effects of bath salts products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presently reported studies may suggest that people recreationally using illicit 'bath salt' products might be at greater risk if their drug use occurs in a warm ambient environment. Common adverse reactions elicited by MDPV overdose in human users include agitation (perhaps analogous to locomotor-stimulant effects in mice), psychosis and violent behavior (perhaps comparable to selfinjurious behavior in mice), hyperthermia (directly observed in mice), and tachycardia (Kyle et al, 2011;Spiller et al, 2011;Borek and Holstege, 2012;Murray et al, 2012), although no studies have yet attempted to correlate symptom severity with ambient temperature. Nevertheless, based upon the present data, we might expect to observe more extreme drug effects if MDPV is administered at higher temperatures.…”
Section: 4-methylenedioxypyrovalerone In Micementioning
confidence: 99%
“…In addition to MDPV, numerous other cathinone analogues, including 4-methylmethcathinone (mephedrone, 4-MMC) and 3,4-methylenedioxymethcathinone (methylone) have been identified in 'bath salt' preparations (Ross et al, 2011;Spiller et al, 2011), but MDPV remains the drug most commonly detected by Emergency Department screens on blood and urine samples from those experiencing untoward effects after exposure to these commercial products in the United States (Kyle et al, 2011;Spiller et al, 2011;Borek and Holstege, 2012;Murray et al, 2012). Despite these indications that MDPV may be a growing public health concern, it remains the case that scant information is available regarding its mechanism of action or in vivo effects.…”
Section: Introductionmentioning
confidence: 99%